22. ASSOCIATED FACTORS OF LOWER GENITAL TRACT INFECTIONS IN WOMEN AGED 15 TO 49 AT TRA VINH OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Introduction: Lower genital tract infections are common in women aged 15 to 49 years and havesignificant impacts on reproductive and overall health.Objective: This study aimed to identify factors related to lower genital tract infections in womenaged 15 to 49 years at Tra Vinh Pediatric Hospital.Research methods: A cross-sectional survey was conducted on 340 women aged 15 to 40 years atthe hospital's outpatient clinic from April to August 2020. The research participants were directlyinterviewed using a structured questionnaire, and outpatient medical records were also observed.Results: Multivariable logistic regression analysis showed that women using intrauterine devices forcontraception were associated with a higher risk of lower genital tract infections, with an odds ratioof 36.00 (95% CI: 1.57 - 826.12).Conclusions: Intrauterine contraceptive methods are independently associated with lower genitaltract infections in women in the study. Although there is still no strong evidence about this causalrelationship in the literature, healthcare professionals should consult women with reproductive healthissues related to contraception and promote their vaginal hygiene practices.
Keywords: Genital tract infection, women, associated factors, intrauterine devices